KECERNAAN DAN FERMENTABILITAS SUBSTRAT KOMBINASI MINERAL– FUNGI DALAM RUMEN - Khanza Syahira Dhia; Kurnia A. Kamil; Hidayat Tanuwira (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
This study aims to determine the digestibility and fermentability of mineral-fungal combinations. The benefit of this study was to obtain data from the digestibility and fermentability of mineral-fungi combinations. The study was carried out in vitro with a completely randomized factorial 2 × 4 design with 3 replications. The variables observed were dry matter digestibility, organic matter digestibility, total VFA production (total volatile fatty acid), and NH3. The data obtained were then analyzed using variance test (ANOVA), if there was an influence on the variables measured, it will be followed by the Tukey’s Studentized Range test. The results showed that the combination of minerals gave a significant effect (P <0.05) and there was an interaction between mineral-fungi (P <0.05) in the digestibility of organic matter and VFA. The highest result was combination mineral with S. cerevisiae and as individual was combination Cu-Sc and Se-Sc. Keywords: Digestibility, Fermentability, Fungi, Mineral, Rumen.